Characterization and measurement of nanostructured copper-based electromagnetic wave absorber. Issue 5 (3rd July 2020) - Rani, Surekha; Marwaha, Anupma; Marwaha, Sanjay; Bindra, Sukhleen; Chavali, Murthy; Reddy, P. Narasimha
ABSTRACT: Nanostructured microwave absorbing materials attract researchers because of their ability to combat electromagnetic (EM) pollution generated by high-speed electronic gadgets without interrupting gadget mobility. In the reported work, the nanosized meta copper material C2101 Kopu Tharma Loham also called nano twin crystalline copper metal fabricated as per ancient Indian metallurgical technology is characterized to ensure its microwave absorbing properties. X-ray diffraction analysis reveals that the particle size of meta copper samples is 100 nm. Further, the melting temperature of meta copper material is 1135ºC higher than copper metal (1085ºC as per International copper standards) making the absorber thermally stable. The EM properties have been experimentally measured through different techniques for frequency ranging from 2 to 40 GHz. The loss tangent plots show that the proposed material performs better in X band. The reflection loss graphs are plotted for different sample thickness values and optimal reflection loss dip of −34.4 dB is obtained at 9.5 GHz for thickness of 2.2 mm. Proposed absorbing material can be integrated on an array substrate for sidelobe level reduction or can be incorporated on aircraft surface for radar cross-section reduction.